Total level and release of silver from a nanoparticles containing dressing used in burns care – a pilot study - Rigo C.; Roman M.; Munivrana I.; Vindigni V.; Azzena B.; Barbante C.; Cairns W. R. L. (E3S Web of Conferences, 2013)
For centuries silver and its compounds have been in use to control infection and avoid septicaemia in the care of burns and chronic wounds. Renewed interest has resulted in a number of silver-based dressings exploiting nanotechnology that are now widely employed in burns centers. Despite extensive use, a systematic study of the chemical composition, release kinetics and biochemical action of these products has yet to be published. In this work we have characterized the morphology and elemental composition of a commercial dressings containing Ag by SEM-EDS. The silver content was determined by ICP-MS to be about 1.4 mg cm-2. Release kinetics in ultra pure water, physiological saline solution and human serum substitute were then deeply investigated. The highest release rates were found in serum substitute, with a maximum of 2.6 μg hr-1 cm-2. Our results show that the mean inhibitory concentrations are exceeded for most common pathogens in serum substitute and sterile water, while the presence of high Cllevels inactivates the dressings.